NILAI-NILAI RELIGIUS DALAM NOVEL “API TAUHID” KARYA HABIBURRAHMAN El SHIRAZY - Lulu Mutamiroh (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
Literature is the result of a portrait of human life in general. The result of human life portrait was modified in various forms literature both poetry and prose. Authors conducted research on novel "Api tauhid" Habiburrahman El Shirazy because the story is about the history that introduces the figure Said Bediuzzaman Nursi. Ingenuity and perseverance in the study also maintained his faith. The focus of this thesis research is to describe the value of religious values in the "Api Tauhid" Habiburrahman El shirazi. The results of this study, the authors found (1) experience the value of religious values (2) the persistence of the main character, in practice the values of religious his faith and (3) a function of experience values religious value of the novel lies in controlling the passions, creating empathy for others, and uplifting life.